Architecture of a wireless sensor network for vital signs transmission in hospital setting - Fariborzi, H.; Moghavvemi, M. (2007)
This paper proposes the architecture of a ubiquitous healthcare system for hospitals and care institutions which is based on application of wireless sensor networks. This system aims to obtain vital signals like ECG and body temperature from multiple patients and transmit it through wireless network to the network coordinator node which is under direct supervision of physician and expert hospital staffs. The wireless nodes that have been utilized for demonstration of the system are tmote sky from Moteiv, which are compatible with IEEE 802.15.4 standard and emerging ZigBee technology for low power applications. To establish and maintain the network for large number of mobile nodes and increase the network lifetime, mesh topology and an energy-aware link-quality-based version of source routing protocol has been used in this system.